Analisis perbandingan peramalan dengan metode least square dan trend moment studi kasus: penjualan produk semen - Sofian, Zoya Inara Dianya; Dewi, Sinta (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to compare the results of forecasting or forecasting sales for July to December 2023 at one of PT's branches. X. PT. X itself sells various kinds of building materials, one of which is cement. As a basic material for building foundations, it is of course the best-selling product, with a presentation of 95.2% of the total turnover of 79,777,000,000. As an effort to control inventory, using forecasting methods as one solution. The forecasting method used is least squares and trend moment. The data collection techniques used were interviews and observation. After carrying out forecasting calculations using two methods, namely least squares and trend moment, make comparisons using Standard Error Forecasting calculations. From the results of the Standard Error Forecasting (SKF) calculation, it is known that the least square method is 764.7496 and the trend moment is 765.3125. Where the results of these calculations show that the best method is the least squares method, so companies are advised to use the least squares method as an effort to control inventory